Sequential Geometric Approach for Device-Free Localization with Outlier Link Rejection. (9th March 2015) - Xiao, Wendong; Song, Biao
Abstract : Device-free localization (DFL) is an emerging technique for estimating the location of the target that does not attach any electronic equipment. Wireless devices are needed to perform as transmitters or receivers. The location of the target is estimated by detecting the changes of the received signal strength (RSS) measurements of the wireless links formed by wireless transmitters and receivers. Due to the uncertainty of the wireless channel, certain links may be polluted seriously, resulting in error detection. In this paper, we propose a novel sequential geometric approach with outlier link rejection (SGOLR) for DFL. It consists of three sequential strategies, including (1) affected link identification by differential RSS detection; (2) outlier link rejection via clustering algorithm by intersection of link (IoL) calculation from the affected links; and (3) density based IoL selection and target location estimation from the remained IoLs. Experimental results show that SGOLR is robust to the fluctuation of the wireless signals with superior localization accuracy compared with the existing Radio Tomographic Imaging (RTI) approach.